2018
DOI: 10.1111/eva.12557
|View full text |Cite
|
Sign up to set email alerts
|

Evolution with a seed bank: The population genetic consequences of microbial dormancy

Abstract: Dormancy is a bet‐hedging strategy that allows organisms to persist through conditions that are suboptimal for growth and reproduction by entering a reversible state of reduced metabolic activity. Dormancy allows a population to maintain a reservoir of genetic and phenotypic diversity (i.e., a seed bank) that can contribute to the long‐term survival of a population. This strategy can be potentially adaptive and has long been of interest to ecologists and evolutionary biologists. However, comparatively little i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(137 citation statements)
references
References 177 publications
8
128
0
1
Order By: Relevance
“…Furthermore, it has been shown that the distribution of activity among a population of starving microorganisms may be highly negatively skewed (i.e., a small number of cells utilizing a large proportion of total energy) (Shoemaker & Lennon, 2017). It is likely, therefore, that simulated POC degradation rates exceed the actual POC degradation rates over this interval, and thus, by extension, simulated microbial maintenance activity is too high.…”
Section: Model Resultsmentioning
confidence: 99%
“…Furthermore, it has been shown that the distribution of activity among a population of starving microorganisms may be highly negatively skewed (i.e., a small number of cells utilizing a large proportion of total energy) (Shoemaker & Lennon, 2017). It is likely, therefore, that simulated POC degradation rates exceed the actual POC degradation rates over this interval, and thus, by extension, simulated microbial maintenance activity is too high.…”
Section: Model Resultsmentioning
confidence: 99%
“…Seed banks also store genetic diversity that provides a source of gene flow from the 310 past (Hairston and Kearns 2002;Vitalis et al 2004;Lundemo et al 2009;Rubio de Casas et al 2015). Maladaptive gene flow from the seed bank can inhibit monopolization by slowing the 312 response to directional selection (Templeton and Levin 1979;Hairston and De Stasio 1988;Shoemaker and Lennon 2018;Tellier 2019), a process we call the 'dormancy load'. 314…”
Section: Evolving Metacommunities With Dormancymentioning
confidence: 99%
“…The above predictions also apply to micro‐organisms (bacteria or fungi) with persistent dormant stages found in soil or in plant microbiomes, albeit with even stronger signatures (e.g. Shoemaker & Lennon, ). The set of current predictions could promote the inter‐disciplinary study of persistent seed banking as a key eco‐evolutionary factor using population genomics, ecology, plant physiology and molecular biology.…”
Section: Resultsmentioning
confidence: 88%